2002
DOI: 10.1021/cm0212109
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Nanoparticles:  Size, Shape, and Self-Assemblies

Abstract: Ruthenium nanoparticles were prepared by reduction of RuCl 3 in a liquid polyol. The mean particle size was restricted to the 1-6 nm range by appropriate choice of the reduction temperature and the acetate ion concentration in the solution. Very narrow particle diameter distributions were obtained. In some samples, among nearly isotropic particles, platelets with aspect ratios as low as 1/4 were detected. Colloidal solutions in toluene were obtained by coating the metal particles with dodecane thiol. Self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
155
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(161 citation statements)
references
References 59 publications
6
155
0
Order By: Relevance
“…Since most of the physical and chemical methods permit prediction of NPs size, they are used as precocious matter in towering technology. Furthermore, they can be used as sample matter for necessary tests that require nonaggregate, homogeneous particles with an expected size and confined size distribution [74]. Additionally, NPs because of their size, display differences in physical and chemical features, which in turn determine changes in optical features which can induce changes in color.…”
Section: Measuring Npsmentioning
confidence: 99%
“…Since most of the physical and chemical methods permit prediction of NPs size, they are used as precocious matter in towering technology. Furthermore, they can be used as sample matter for necessary tests that require nonaggregate, homogeneous particles with an expected size and confined size distribution [74]. Additionally, NPs because of their size, display differences in physical and chemical features, which in turn determine changes in optical features which can induce changes in color.…”
Section: Measuring Npsmentioning
confidence: 99%
“…The resulting metal NPs can be filtered and dried in air. The polyol method has been used in the presence of various stabilisers such as dodecane-thiol as a capping agent [38], or supports such as polyvinylpyrrolidone (PVP) [39][40][41][42] and -alumina [26].…”
Section: Synthesis and Characterisation Of Ru-nps In Ionic Liquidsmentioning
confidence: 99%
“…It has been reported that cadmium substituted Cu ferrites behaves as n-type semiconductors and the seebeck coefficient gradually decreases with increase in cadmium content [12,13]. The physical and chemical properties of these materials can be tuned by controlling the particle size, shape and the inter particle interactions [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%